PENGUATAN SPIRITUALITAS ISLAM MELALUI BUDAYA PROFETIK - Roqib, Mohamad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Purwokerto, 2011)
This article describes prophetic culture which is implemented to Javanese society. There are three important pillars, namely transcendence, liberation, and emancipation. These pillars are understood clearly and elaborated in detail. Those indicators are used as the guidance on implementing a more dignified human life.